Amazonglês: uma proposta para aprendizagem significativa de vocabulário em inglês no ensino fundamental - Mendes, Isabella Marcela Teixeira Laborda (2024)
This research aims to evaluate a potentially significant teaching unit, called Amazonglês, designed to mediate the teaching-learning process of English vocabulary. The proposal was applied to elementary school students from a public school in the city of Manaus. The research has as its theoretical support the Theory of Meaningful Learning, based on authors such as Ausubel (2000) and Moreira (2012) and scholars such as Scaramucci (1995), Gattolin (2005) and Leffa (2000) regarding vocabulary learning. The methodological procedures involve qualitative, exploratory research and use of the case study method (Yin, 2015). Data collection was carried out with the aid of a questionnaire, participant observation and an observation grid, focusing on the analysis of two criteria: motivation and performance, the latter being used to evaluate the control and range of vocabulary learning. Data from assessments carried out in three stages were also included: pre-test to verify prior knowledge, post-test and late post-test (Zilles, 2001). Data analysis was carried out using the Content Analysis method, along the lines of Bardin (2016). The results showed that the proposal contributed significantly to learning vocabulary in English. As for the results, we highlight the potential of the Amazonglês proposal so that students can take ownership of their regionality and reflect on the importance of learning vocabulary for their school, personal and professional lives. Regarding potentially significant activities, we highlight mind maps. The use of mental maps contributed to the expansion of the repertoire presented in the UEPS, which was validated through the creations and quantity of new words present in the activity. In the control and range criteria, it was possible to observe a progression in learning, considering the little prior knowledge about specific vocabulary and the significant amount of vocabulary retained in memory (with post-test and late post-test). The educational product arising from this research is a teaching guide aimed at English teachers, with guidelines and possibilities for activities to be developed with a focus on teaching and learning vocabulary supported by the Meaningful Learning theory.